Photon parameters for γ-rays sensing properties of some thick oxide films - Kavanoz, H. Birtan; Yagci, Ozlem; Yalcin, Zeynel; Icelli, Orhan; Altindal, Ahmet; Okutan, Mustafa; Mann, Kulwinder Singh (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
This study aimed at determining gamma-rays sensing properties of some thick oxide films (LiCoO2, TiO2, Cr2O3, Nb2O5, NiO, ZnO, Zn2SnO4, SnO2, CeO2, SmFeO3, SmCoO3, WO3, In2O3) in energy range of 0.015-15 MeV by calculating total mass attenuation coefficients (mu/rho), effective atomic numbers (Z(eff)) and effective electron densities N-el,N-eff. In addition, the energy absorption (EABF) and exposure (EBF) build-up factors have been calculated for these samples within the same energy range and up to the penetration depth of 40 mean free paths (mfp). The computed EABF and EBF are useful for extensive utilization of design in radiation shields and gas sensors. The result of the calculations revealed that the Zn2SnO4 oxide film exhibited superior gamma-rays sensing response in the wide energy range. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Gamma-rays sensors; Effective electron density; Thick oxide films; EFFECTIVE ATOMIC NUMBERS; TROMMEL SIEVE WASTE; ELECTRON-DENSITIES; SOL-GEL; ATTENUATION COEFFICIENTS; AMINO-ACIDS; GAS SENSOR; SILICON; SUPERCONDUCTOR; SELECTIVITY; Materials Science; Physics